2020
DOI: 10.1177/0021998319897407
|View full text |Cite
|
Sign up to set email alerts
|

Bi-tubular corrugated composite conical–cylindrical tube for energy absorption in axial and oblique loading: Analysis and optimization

Abstract: In this paper, a new bi-tubular corrugated composite tube, consisting of inner and outer cylindrical and conical tubes is proposed. Different models with various geometrical parameters including the radius of curvatures and their numbers are considered and studied numerically in axial and oblique crushing in order to achieve favorable crashworthiness parameters. Moreover, quasi-static compression tests have been conducted to obtain results in order to validate the finite element model. There has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 57 publications
0
8
0
1
Order By: Relevance
“…The material model 'MAT54_ENHANCED_COMPOSITE_DAMAGE', is utilized to model the composite tubes in this study, with the properties of unidirectional T300/PC105 as displayed in Table 2. 34…”
Section: Finite Element Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The material model 'MAT54_ENHANCED_COMPOSITE_DAMAGE', is utilized to model the composite tubes in this study, with the properties of unidirectional T300/PC105 as displayed in Table 2. 34…”
Section: Finite Element Modelmentioning
confidence: 99%
“…[26][27][28][29][30][31][32] In one of the studies, corrugated cylinders were numerically investigated by Mahbod and Asgari, showing better crashworthiness than straight tubes. 33 Sadighi et al 34 researched into the energy absorption capacity of foam-filled bitubular conical-cylindrical tubes, which displayed much higher energy absorption capacity than their bi-tubular straight tubes. Alkhatib et al 35 looked into the crushing response of CFPR and KFRP composite tubes, which were filament-wound on ABS wedge-like corrugated mandrels and failure modes were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Also, they created a three-dimensional finite element model based on continuum damage mechanics to estimate the ultimate loadbearing capacity and failure mechanism. Sadighi et al 18 suggested a novel bi-tubular corrugated composite tube composed of inner and outer cylindrical and conical tubes. Several models with varying geometrical dimensions were explored and evaluated numerically in axial and oblique crushing to obtain acceptable crash worthiness parameters.…”
Section: Introductionmentioning
confidence: 99%
“…17 Also, a new bi-tubular corrugated composite tube, consisting of inner and outer cylindrical and conical tubes is considered and studied numerically in axial and oblique crushing in order to achieve favorable crashworthiness parameters. 18 The crushing behavior of hybrid metal-composite conical tube under dynamic loading is studied by Shiravand and Asgari 19 and a theoretical solution for laminated composite conical tubes is developed.…”
Section: Introductionmentioning
confidence: 99%